Kubernetes for Developers: Use Kubernetes to Develop, Test, and Deploy Your Applications with the Help of Containers - Heck, Joseph (Packt Publishing, Limited, 2018)
Kubernetes provides a means to describe what your application needs and how it should run by orchestrating containers on your behalf to operate your software across a single, dozens, or hundreds of machines. Originally created and open sourced from Google, you can use their technology to help run, test, and scale your applications regardless.